The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1088/1361-648x/ac6a99
|View full text |Cite
|
Sign up to set email alerts
|

Structural, dynamic, and hydration properties of quercetin and its aggregates in solution

Abstract: Quercetin is a flavonoid present in the human diet with multiple health benefits. Quercetin solutions are inhomogeneous even at very low concentrations due to quercetin's tendency to aggregate. We simulate, using molecular dynamics, three systems of quercetin solutions: infinite dilution, 0.22 M, and 0.46 M. The systems at the two highest concentrations represent regions of the quercetin aggregates, in which the concentration of this molecule is unusually high. We study the behavior of this molecule, its aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…Quercetin is a widely consumed flavonoid and is abundant in the human diet. Mario Campo and Griselda Corral have studied with the help of molecular dynamics simulation quercetin solutions at three different concentrations [27]. The authors have identified the hydrophobic and hydrophilic regions of the quercetin molecule and have observed its effect on the water structure.…”
Section: Biological Soft Matter Systemsmentioning
confidence: 99%
“…Quercetin is a widely consumed flavonoid and is abundant in the human diet. Mario Campo and Griselda Corral have studied with the help of molecular dynamics simulation quercetin solutions at three different concentrations [27]. The authors have identified the hydrophobic and hydrophilic regions of the quercetin molecule and have observed its effect on the water structure.…”
Section: Biological Soft Matter Systemsmentioning
confidence: 99%